Respuesta :
x = -11/6
First multiply (-2/3) by (3x-4).
your equation should now be -2x + (8/3) +3x = (5/6)
combine the x terms and subtract 8/3 to the other side
Answer: The required solution for x is [tex]-\dfrac{11}{6}.[/tex]
Step-by-step explanation: We are given to solve the following equation for x :
[tex]-\dfrac{2}{3}(3x-4)+3x=\dfrac{5}{6}~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
To solve the given equation for x,
we must take all the terms involving x on the left-hand side and the other constant terms on the right-hand side of the equation.
The solution of equation (i) is as follows :
[tex]-\dfrac{2}{3}(3x-4)+3x=\dfrac{5}{6}\\\\\\\Rightarrow -2x+\dfrac{8}{3}+3x=\dfrac{5}{6}\\\\\\\Rightarrow x=\dfrac{5}{6}-\dfrac{8}{3}\\\\\\\Rightarrow x=\dfrac{5-16}{6}\\\\\\\Rightarrow x=-\dfrac{11}{6}.[/tex]
Thus, the required solution for x is [tex]-\dfrac{11}{6}.[/tex]